REVIEW : CATALITIC CONVERTER BERBAHAN TEMBAGA (Cu) DAN KUNINGAN / BRASS (CuZn) UNTUK MEREDUKSI KARBON MONOKSIDA (CO) DAN HIDROKARBON (HC) EMISI GAS BUANG PADA KENDARAAN BERMOTOR - Basyari, Aziz; Pranoto, Hadi (Universitas Muhammadiyah Metro, 2024)
Motor vehicle exhaust emissions containing carbon monoxide (CO) and hydrocarbons (HC) are a strategic issue for Indonesia, which has not yet set an age limit for motor vehicles. As a control measure, the Indonesian government itself has issued regulations on exhaust gas emission quality standards for motorized vehicles that are used by the public through Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number 8 of 2023. Catalytic converter technology is the most effective system for reducing CO and HC emissions. Currently, it is from the Platinum Gold Metal (PGM) group, namely Platinum, Palladium, Rhodium which is still very expensive. This article uses a literature review research method with reference sources originating from previous research journals by comparing. This paper will discuss gas emissions, the development of converter catalytic materials and also the effectiveness of converter catalytic materials from the non-PGM metal group, namely Copper (Cu) and Brass/ Brass (CuZn) which has been proven to be able to reduce exhaust gas emissions so that it can be an alternative as a converter catitic at a more affordable price for the wider community